Racial disparities in treatment preferences for rheumatoid arthritis - Constantinescu, Florina; Goucher, Suzanne; Weinstein, Arthur; Fraenkel, Liana (Medical care, 2009)
Data suggest that differences in patient preferences may account for racial disparities in the use of medical interventions. Racial disparities have also been noted in outcomes and the delivery of healthcare services in chronic disease. Whether treatment preferences in chronic disease differ by race is not known. We elicited treatment preferences for aggressive therapy in patients with rheumatoid arthritis who identified themselves as being black or white. One hundred fifty consecutive eligible patients were invited to participate. Of these, 136 subjects completed the interview. In unadjusted analysis, 51% of white participants preferred aggressive therapy compared with 16% of blacks (P < 0.0001). Subjects who were married and reported having at least some college education had stronger preferences for aggressive therapy compared with their respective counterparts. After adjusting for covariates, race remained the strongest predictor of aggressive therapy examined in this study [adjusted odds ratio (95% confidence interval) = 11.2 (1.9-64.9)]. In this study, fewer black patients preferred aggressive treatment compared with white patients with similar disease severity. These results have important clinical implications because use of aggressive treatment improves both short- and long-term outcomes in rheumatoid arthritis. Efforts to improve patient education and physician communication should be made to ensure that all patients have an accurate understanding of the benefits, as well as risks, associated with the best available treatment options.